Patterns of progression differ between Kellgren-Lawrence 2 and 3 knees fulfilling different definitions of a cartilage-meniscus phenotype in the Foundation for National Institutes of Health Osteoarthritis Biomarkers study (FNIH). Issue 3 (September 2022) - Roemer, Frank W.; Collins, Jamie E.; Hunter, David J.; Demehri, Shadpour; Guermazi, Ali
Abstract: Objective: Aim was to describe three definitions for an MRI-defined cartilage-meniscus phenotype and to report phenotypic progression in Kellgren-Lawrence (KL) 2 and 3 knees over 48 months. Methods: The study sample was a nested case-control study with knees showing either 1) radiographic and pain progression ("composite" case), 2) radiographic progression only, 3) pain progression only, and 4) no progression. MRI was performed on 3T systems. MRIs were read according to the MOAKS system. Knees were classified as having the cartilage-meniscus phenotype according to three modified ROAMES (Rapid OsteoArthritis MRI Eligibility Score) definitions (D): 1) ​≤ ​2.2 (10–75% of the region of cartilage surface area with 10–75% affected by full thickness loss), i.e. 'D1' 2) ≤ 2.1 (10–75% of the region of cartilage surface area with <10% affected by full thickness loss), i.e. 'D2' and 3) ≤ 2.0 (10–75% of the region of cartilage surface area without full thickness loss), i.e. 'D3'. The odds of being a composite case for those with vs. without each definition was determined using logistic regression. Results: 485 knees were included. For KL2 knees 191 (64%) knees fulfilled D1 criteria, 183 (62%) D2 and 167 (56%) D3. For KL3 these numbers were 164 (87%), 103 (55%) and 77 (41%). Odds for being a composite case for KL2 knees were 2.52 (95% CI 1.40, 4.54) for D1, 1.93 (95% CI 1.11, 3.35) for D2 and 1.92 (95% CI 1.13, 3.28) for D3. For KL3 knees odds were 0.32 (95% CI 0.13, 0.78) for D1, 0.56 (95% CI 0.31, 1.01) for D2 and 0.49 (95% CI 0.26, 0.91) for D3. Conclusion: Increased odds for progression are seen for KL2 knees for all definitions, while this was not observed for KL3 knees. KL3 knees exceeding the maximum damage thresholds and not fulfilling the phenotypic definitions are still likely to experience further progression.